Fertility Decline in Algeria 1980-2006 : A Case Study - World Bank (World Bank, Washington, DC, 2017)
Like other countries in the Middle East and North Africa region, Algeria has undergone a demographic transition. But Algeria's fertility decline defies conventional explanation. Despite inauspicious starting conditions-a high total fertility rate, reluctant policy environment, and delayed implementation of a national family planning program-Algeria has surpassed some of its neighbors in fertility reduction. Before its fertility transition, Algeria had one of the highest crude birth rates in the world, nearly 50 per 1,000. The fertility transition began in 1965-70, before any significant government support for or investment in population control or family planning and before significant external donor funding became available. Since then, profound changes in the traditional family model have led to a 64 percent decline in the total fertility rate in recent decades, from 6.76 in 1980 to 2.41 in 2006. Overall, Algeria's fertility decline is best understood in terms of changes in behavior, especially the delay in age at first marriage, the increase in contraceptive use, and-to a certain degree-the negative effects of the economic crisis manifested in the housing shortage and unemployment of young adults.